Solvability of cubic equations over Q3 - Mansoor Saburov,; Mohd Ali Khameini Ahmad, (Universiti Kebangsaan Malaysia, 2015)
We provide a solvability criterion for a cubic equation in domains Z3, Z3, and Q3.